2007
DOI: 10.1111/j.1468-1331.2006.01541.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variants in Bulgarian patients affected by multiple sclerosis

Abstract: The occurrence of multiple sclerosis (MS) in subjects clustering to a particular mitochondrial DNA (mtDNA) haplogroup/haplotype or carrying mtDNA mutations associated with Leber's hereditary optic neuropathy (LHON) has suggested that mitochondrial genome may contribute to susceptibility to MS. In the present study, 58 unrelated Bulgarian patients with relapsing remitting form of MS and 104 randomly selected healthy individuals were analysed for the presence of 14 mtDNA polymorphisms determining major European … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
(36 reference statements)
0
14
1
2
Order By: Relevance
“…Our results differ to those reported in a recent study in Bulgarian multiple sclerosis patients which showed evidence for an association with the secondary LHON mutation 4216C [19]. In the present study the 4216C allele was present in 24.3% and 27.2% of cases and controls respectively (p = 0.5256), the observed trend being in the opposite direction to that identified in the Bulgarian study [19].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results differ to those reported in a recent study in Bulgarian multiple sclerosis patients which showed evidence for an association with the secondary LHON mutation 4216C [19]. In the present study the 4216C allele was present in 24.3% and 27.2% of cases and controls respectively (p = 0.5256), the observed trend being in the opposite direction to that identified in the Bulgarian study [19].…”
Section: Discussioncontrasting
confidence: 99%
“…The data regarding haplogroups have been somewhat contradictory with some researchers suggesting that haplogroups K and J increase risk [17], [21] while others have found evidence that haplogroup J/T is protective [18]. The possible relevance of LHON related mutations has understandably received attention and a suggestion that secondary LHON mutations (mutations which are more common in LHON but are not directly pathogenic for the condition) increase the risk of multiple sclerosis has been suggested [9], [13], [19], [22] whilst another study showed a decreased risk [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are reports of mitochondrial DNA polymorphisms in particular individuals and subgroups of MS patients (42, 43), it is considered unlikely that mitochondrial DNA mutations are widely associated with typical forms of MS (44). However, a relationship between MS disease progression and acquired mitochondrial dysfunction secondary to inflammation-induced damage to the mitochondrion has been hypothesized (5).…”
Section: Discussionmentioning
confidence: 99%
“…Vanopdenbosch et al (2000) showed that the association of LHON and MS is more than a coincidence. Mihailva, showed that mutation of T4 216C may be predisposing marker for MS (Mihailova et al 2007). In our study, the most prevalent mutations were J, L, and T. This result is the same as another report from Iranian patients , and these haplogroups may be a predisposing factor for MS in Iranian patients.…”
Section: Discussionmentioning
confidence: 99%